THE 2017 LABOR REFORM: THE WEAKENING OF TRADE UNIONS AND THE CORRELATION OF STRENGTH BETWEEN EMPLOYEES AND EMPLOYERS (CIPEEX, 2025)
The objective of this work is to analyze the impacts of the 2017 Labor Reform on union representation in Brazil. Over the last seven years, there has been a significant weakening of trade unions, essential tools in the fight for workers' rights. Using the literature review method, it was possible to see that the labor reform introduced changes in the Consolidation of Labor Laws, which affected the protection and rights of workers, further unbalancing the relationship between employees and employers. One of the results found was that the extinction of mandatory union contributions drastically reduced the revenue of trade unions and limited their ability to mobilize and maintain physical structures. This resulted in the reduction of professional staff in several unions across the country. The search for financing alternatives and union strengthening strategies is crucial. The resumption of union strength depends not only on political or legislative changes, but also on the adoption of new approaches, such as the strategic use of social networks, the search for partnerships, and constructive dialogue between unions, government, employers, and workers. Union representation by economic categories emerges as a dynamic tool to face contemporary challenges, allowing a deeper understanding of the needs of workers in different sectors. It was concluded that the union of the working class and the strengthening of trade union organizations are essential to guarantee decent and fair working conditions in a socioeconomic scenario in constant transformation.
Keywords: Labor Reform; Union Contribution; Union Strengthening